Copper conductive patterns through spray-pyrolysis of copper-diethanolamine complex solution. - Jutamart Chotipanich; Suraya Hanim Abu Bakar; Amornchai Arponwichanop; Tetsu Yonezawa; Soorathep Kheawhom (PLoS ONE)
A simple and low-cost method to fabricate copper conductive patterns at low temperature is critical for printed electronics. Low-temperature spray-pyrolysis of copper-alkanolamine complex solution shows high potential for this application. However, the produced copper patterns exhibit a granular structure consisting of connected fine copper particles. In this work, low-temperature spray-pyrolysis of copper formate-diethanolamine complex solution under N2 flow at a temperature of 200 °C was investigated. The effects of spraying conditions on microstructure and electrical properties of the patterns were examined. Our results revealed that the spraying rate is a critical parameter determining the degree of sintering and electrical resistivity of the patterns. A low spraying rate facilitates sintering, and hence well-sintered copper patterns with the lowest resistivity of 6.12 μΩ.cm (3.6 times of bulk copper) on a polyimide substrate could be fabricated.